2015
DOI: 10.1111/jog.12899
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of polyvinylidene fluoride and polypropylene suburethral slings in the treatment of female stress urinary incontinence

Abstract: Aims Evaluate the effectiveness and safety of polyvinylidene fluoride (PVDF) transobturator suburethral slings/tapes (TOTs) in the treatment of stress urinary incontinence, and compare them to polypropylene (PP) slings. Material and Methods A retrospective cohort study was performed on women treated with a TOT procedure at Vall d'Hebron Hospital between February 2010 and May 2013. A PVDF sling was used in surgeries on 23 women. A comparison group was randomly selected among all women treated with a PP sling in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
(39 reference statements)
7
6
0
Order By: Relevance
“…The amount of foreign body reaction and the consequent mesh contraction 13,22 could explain some cases of de novo UUI. In addition, the overall rates of de novo UUI are similar to those described previously 15,23 . On the contrary, we have not found the differences in obstructive events observed previously, 15 nor in other complications.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The amount of foreign body reaction and the consequent mesh contraction 13,22 could explain some cases of de novo UUI. In addition, the overall rates of de novo UUI are similar to those described previously 15,23 . On the contrary, we have not found the differences in obstructive events observed previously, 15 nor in other complications.…”
Section: Discussionsupporting
confidence: 89%
“…In a previous descriptive clinical study we found similar effectiveness and complications with PP and PVDF slings, although more obstructive events were observed in the PP group 15 . However, to date there are no clinical trials comparing those materials in suburethral slings.…”
Section: Introductionsupporting
confidence: 50%
“…There is a paucity of data in literature regarding the use of PVDF slings in urinary incontinence procedures. While Padilla-Fernandez et al reported less tolerance and less success rates of PVDF slings in TOT procedures (35), Sabadell et al demonstrated similar efficacy and safety of PVDF slings with polypropylene slings (36). Currently, there are no studies that compare PVDF with polypropylene SIS.…”
Section: Discussionmentioning
confidence: 99%
“…We resorted to PVDF because we already used it for a commonly associated procedure (rectopexy) and prolapse surgery . PVDF is also used for hernia repair and urinary slings . There are several theoretical advantages of PVDF over PP, yet comparative clinical data are scarce.…”
Section: Discussionmentioning
confidence: 99%